Determinants of Financial Performance of Microfinance Institutions in India - Gakhar, Kamlesh; Meetrl, (Gyan Management Journal, 2014)
Nowadays, the issue of financial sustainability ofmicrofinance institutions (MF!s) has captured the attention of many researchers due to its importance in the livelihood of microfinance institutions. Institutional sustainability also depends on the financial sustainability of microfinance institutions. To ensure the sustainability of MF/s, many strategies have been put in place. This highlights the importance of sustainable microfinance and need to search for the means to make an MF/ sustainable. The present work is an attempt to analyze the factors affecting the performance of MF ls from a sample of 40 MF/s for the year 2011. The study showed that the regulatory provisions and the size of the loan are the factors positively affecting the performance of MFis. However, borrowers cost, portfolio size and the age of an MFI negatively affects its performance. Thus, the recent regulation imposed by Malegam committee may work as an opportunity for the microfinance institutions.
Keywords: Microfinance Institutions; ROA; Breadth of outreach; Depth of outreach; sustainability